Price adjustments on the Johannesburg Stock Exchange for unexpected and dramatic news events: An empirical analysis - N. Bhana (South African Journal of Business Management, 1989)
The objective of this study is to determine whether companies listed on the Johannesburg Stock Exchange overreacted to unexpected favourable and unfavourable company-specific news events during the period 1970 - 1984. The JSE appears to be inefficient in reacting to the announcement of unfavourable news; economically significant abnormal returns up to one year following the event are observed. The JSE does not appear to overreact to news of a favourable nature, there is only weak evidence of short-term overreaction. The selling pressure caused by panic selling could depress prices well below levels justified by the unfavourable news. The magnitude of the overreaction to unfavourable news is sufficient to enable astute investors to outperform the market by taking positions in these securities. Knowledge of the pattern of market overreaction can also be of value to investors for transactions that are to take place anyway.
Keywords: 650